Study of the impact of atopic dermatitis in children on the quality of life of families - O. Mozyrska (Zaslavsky O.Yu., 2023)
Background. Atopic dermatitis is a chronic, relapsing eczema. Although atopic dermatitis occurs mainly in children, it greatly affects the life of the whole family. The purpose was to assess the quality of life of the families of children with atopic dermatitis and to study the correlation between the severity of atopic dermatitis and the quality of life of family members according to the Family Dermatology Life Quality Index (FDLQI) questionnaire. Materials and methods. The study included 104 patients with atopic dermatitis aged 6 months to 17 years (median of 6 [3; 9] years) who were treated at the Allergy Department of the Kyiv City Children's Clinical Hospital 2. Clinical parameters included age, sex of the patients, disease duration and severity of atopic dermatitis. The latter was assessed by the SCORing for Atopic Dermatitis (SCORAD) tool. Spearman's rank correlation index was used for analysis of correlation between FDLQI and SCORAD indicators. Р < 0.05 was considered statistically significant. Results. The quality of life of the family of 104 children with atopic dermatitis was assessed using the FDLQI questionnaire. Four parents (3.8 %) reported no impact of the disease on the family's quality of life, 65 (62.5 %) - a mild effect, 34 (32.7 %) - a moderate impact, parents of 1 patient (1.0 %) noted a very large effect. The average FDLQI was 6.4 ± 2.8. There was a correlation between the FDLQI and the SCORAD severity index (Ro = 0.714, p < 0.01). In the subgroup of children under 4 years of age, a strong correlation between the FDLQI and the SCORAD was found (Ro = 0.789, p < 0.01). Child's age and disease duration were not associated with the quality of life score (Ro = -0.011, p > 0.05 and Ro = 0.076, p > 0.05, respectively). In the subgroup of children aged 4-17 years, a strong positive correlation of FDLQI and the SCORAD was also determined (Ro = 0.714, p < 0.01). The age of the children and the duration of the disease were not related to the quality of life score (Ro = -0.011, p > 0.05 and Ro = -0.027, p > 0.05, respectively), although in the subgroup of younger children (4-7 years) we noted a tendency towards a greater influence of the disease on the family's quality of life. Conclusion. In this study, most parents of children with atopic dermatitis reported a mild to moderate impact of the disease on their quality of life. The FDLQI of family members correlated with the severity of atopic dermatitis.